Espalhamento Raman dependente da temperatura em cristais de ácido dl-aspártico - Fernandes, César Rodrigues (2010)
This dissertation presents the results of Raman scattering in crystals of DL-aspartic acid under various temperature conditions. The DL-aspartic acid (C4H7NO4) crystallizes in space group C2h 6 with eight molecules per unit cell, so there are 128 atoms in the unit cell that give rise to 384 normal modes of vibration. Of these modes a total of 192 modes are Raman active, which could be observed in not polarized spectra, but by various factors only some of these modes are observed. We did an attempt identification of all normal modes of vibration that appears in the spectral range between 50 and 3200cm-1 and a study with variation in temperature between 10 and 433 K. The interval between 0 and 150 cm-1 is extremely important for detection of phase transitions because it contains the structural modes of vibration of the lattice. In the case of DL-aspartic acid there was a reversal of intensity for the modes at 82 and 87 cm-1, in considering the extremes of temperature interval measured. This reversal was interpreted as a small conformational change, not associated with a phase transition. With exception of this reversal there were not anomalies, not appearance or disappearance of modes in this region, which pointed to the stability of the material. Another event occurred in this region: the bands at 116 and 132 cm-1, very different at very low temperatures (< 150 K) become indistinguishable at 200 K. This fact can not be associated with a phase transition because the broadening of bands, arising from increasing temperatures, implies the superposition of modes. Added to this there is the fact that the torsional vibrations of the NH3 + and rocking of CO2 - (modes associated with hydrogen bonds) behaved linearly in frequency-temperature curves. Finally we did a study of differential scanning calorimetry, which confirmed what had been observed by Raman spectroscopy - the stability of the structure throughout the temperature range investigated.